2006
DOI: 10.1038/sj.emboj.7600999
|View full text |Cite
|
Sign up to set email alerts
|

14-3-3 proteins integrate E2F activity with the DNA damage response

Abstract: The E2F family is composed of at least eight E2F and two DP subunits, which in cells exist as E2F/DP heterodimers that bind to and regulate E2F target genes. While DP-1 is an essential and widespread component of E2F, much less is known about the DP-3 subunit, which exists as a number of distinct protein isoforms that differ in several respects including the presence of a nuclear localisation signal (NLS). We show here that the NLS region of DP-3 harbours a binding site for 14-3-3e, and that binding of 14-3-3e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 46 publications
2
22
0
1
Order By: Relevance
“…wt, wild type (14-3-3ε ϩ/ϩ ); mut, mutant (14-3-3ε Ϫ/Ϫ ). (35), and knockout of both E cyclins in mice leads to cardiac defects, including VSDs (15). p27 Kip1 -null mice display increased numbers of cardiac myocytes, with fewer cells in the G 0 /G 1 phase (46), findings that are consistent with our results and suggest that increased levels of p27…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…wt, wild type (14-3-3ε ϩ/ϩ ); mut, mutant (14-3-3ε Ϫ/Ϫ ). (35), and knockout of both E cyclins in mice leads to cardiac defects, including VSDs (15). p27 Kip1 -null mice display increased numbers of cardiac myocytes, with fewer cells in the G 0 /G 1 phase (46), findings that are consistent with our results and suggest that increased levels of p27…”
Section: Discussionsupporting
confidence: 90%
“…We cannot rule out the possibility that suppression of the G 2 /M phase at E12.5 (Fig. 4i) results not only from the accumulation of cardiomyocytes in the G 0 /G 1 phase but also from impairment of proteins driving mitosis, such as Cdc25C and Cdk1 (17,35).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests that it plays a role in diverse biochemical Heat shock protein 8 activities related to signal transduction, such as cell division, apoptosis and the regulation of insulin sensitivity (28)(29)(30). Studies have suggested that the cleavage of YWHae during apoptosis promotes cell death and induces cell cycle G2 arrest (30); while apoptosis was induced by the expression of e2F, it was less significant in the presence of YWHAE. RRM1, a prb/e2F cell-cycle target gene (31), encodes one of two nonidentical subunits that constitute ribonucleoside-diphosphate reductase, an enzyme essential for the production of deoxyribonucleotides prior to dna synthesis in the S phase of dividing cells.…”
Section: Discussionmentioning
confidence: 99%
“…32 The loss of 14-3-3-sigma contributes to tumorigenesis in different tissues including prostate. 33 Compared to DN-ANXA7, WT-ANXA7 upregulated 14-3-3-sigma that was shown to be induced by p53.…”
Section: Anxa7 Protein Affected Cell Viability In Prostate Cancer Celmentioning
confidence: 99%